Control Directo al Par y Control de Campo Orientado para un Motor Síncrono de Imanes Permanentes - Cuji, William David; Arcos Avilés, Diego (Ingeniería, 2019)
Context: The permanent magnet synchronous motors (PMSM) have rapidly improved their performance in terms of power density, efficiency, and better dynamics, thanks to the technologies used in them, such as: the control technique and the drive circuit technology. A PMSM can operate both as a motor and as a generator. In addition, they stand out for having a low maintenance, since unlike other types of engines the PMSM does not have collector rings or brushes. The control algorithm that is generally used in this type of motor is a vector control, which is divided into Direct Torque Control (DTC) and Field Oriented Control (FOC). Method: The computational platform where the simulations are carried out is MatlabR software (R2017a) Simulink 8.9, where predetermined blocks and program functions are used for the DTC and FOC vector control diagrams. Results: Regarding the electromagnetic torque control, FOC presents higher ripple than the DTC, so that, it is concluded that the DTC has greater torque control in relation to the FOC. Regarding to the magnetic flux control, according to the obtained values, the DTC has better control performance than the FOC. For speed control, both the DTC and FOC control have a fast response to disturbances; however, the DTC has a fast control response when the PMSM starts moving from rest, which means that the DTC has a faster response in the transient state and when the engine is in motion FOC has better control performance to disturbance. Conclusions: When analyzing the most important aspects to determine which control technique is effective, it is concluded that the DTC control technique has greater effectiveness with respect to the FOC control technique. However, it is worth mentioning that the two control techniques are widely used in the industrial sector for driving electric motors, so that, the selection any of these techniques Will depend on the process to be carried out.